Digital philanthropy for the masses: crowdfunding platforms marketising NGO partnerships for individual giving in India. Issue 7 (3rd October 2021) - Banerjee, Shonali Ayesha
ABSTRACT: This article demonstrates the complex role digital crowdfunding platforms play in non-profit fundraising, exploring the nebulous area they occupy when partnered with NGOs in India. Using data from platforms GlobalGiving and Impact Guru to identify the complicated partnerships between platforms and NGOs, it examines the problematic nature of marketised fundraising models. By advocating competitive and technologised practices, crowdfunding platforms create tensions between themselves and their NGO partners, who are forced to continuously adjust and innovate their fundraising strategies. Given their emphasis on profit generation, this article argues that digital platforms limit their intention to create inclusive fundraising spaces for NGOs.